The indigenous issue and the current Brazilian State (Research, Society and Development, 2022)
This paper outlines the tension between the indigenous issue and the Brazilian State, drawing from Foucauldian concepts of power and Mbembians on Necropolitics, a discussion between the State and capitalism in the Brazilian context, in line with the Marxist sphere. The research is delimited between the years 2019/2022 referring to the presidential term of the current federal government that adopts a policy contrary to indigenous interests and a government power discourse against the rights guaranteed in the Federal Constitution and laws, with the use of the state machine in environmental actions and measures of aggression to the environment and indigenous peoples. The objective is to propose a dialogue and contribute to the debate on the power relations that permeate the social, political and economic life of the State over native peoples. The method used is in qualitative exploratory bibliographic research on the main works on the subject and critical and analytical reflection of the data researched. It is concluded that the federal government between the years 2019/2022 uses the structure of the State to achieve consecrated rights of indigenous peoples, giving preference to holders of economic power violating the Federal Constitution of 1988 and the laws.